Walk 5 TRAM NUMBER 5 - -, - (project baikal, 2011)
Water Sports Complex Residential Complex on Dybovsky Street Administrative Building of OOO “Gazprom Dobycha Irkutsk” Variable-Story Development (behind Sun Hotel) Sports Complex “Empire of Sports”